Antibiotic susceptibility of cultivable aerobic microbiota from the oral cavity of Echis carinatus from Odisha (India). (June 2020) - Padhi, Laxmipriya; Panda, Sujogya Kumar; Mohapatra, Pratyush P.; Sahoo, Gunanidhi
Abstract: During a snake bite, the microbes may get transferred to the bite site and may cause secondary infection along with envenomation. The knowledge on the oral bacterial flora of snakes constitutes information important for snake bite management. The inadequately studied oral microflora of snakes differ geographically, temporally and among the members of the same species. The objective of this study is to determine the pattern of oral bacterial flora of Saw-scaled viper ( Echis carinatus ) and their susceptibility to antibiotics. Oral swabs were collected from nine healthy Saw-scaled vipers, subjected to microbiological, biochemical and molecular characterization. Additionally, these isolates were subjected to antimicrobial susceptibility testing using ICOSA-20-Plus and ICOSA-20-Minus. A wide range of pathogenic bacteria such as Salmonella arizonae, Pseudomonas stutzeri, Proteus penneri, Alcaligenes faecalis; Citrobacter diversus, C. freundii, Enterococcus faecalis, Bacillus anthracis, Staphylococcus sciuri and Achromobacter xylosoxidans were isolated as new additions to the floral diversity of saw scale viper. Most of the isolates were sensitive towards amikacin, azithromycin, imipenem, ciprofloxacin, gentamicin, ofloxacin, sparfloxacin, tobramycin, levofloxacin, kanamycin, tetracycline, and chloramphenicol while resistant to amoxyclav, cephalothin, cefpodoxime, Co-Trimoxazole, oxacillin and penicillin. The present study revealed that the bacterial flora of the oral cavity of Saw-scaled viper is resistant to many common antibiotics, which are often used for the treatment of snake-bite victims. Highlights: Oral cavity of Echis carinatus harbours diverse pathogenic bacteria. Majority of isolates were sensitive to penicilin, Amoxyclav, cefpodoxime ampicillin and methicillin. Azithromycin, gentamicin, ciprofloxacin, imipenem, etc are most sensitive antibiotics.